Clinical considerations and recommendations for OCT-guided carotid artery stenting. (2nd April 2020) - de Donato, Gianmarco; Pasqui, Edoardo; Alba, Giuseppe; Giannace, Giovanni; Panzano, Claudia; Cappelli, Alessandro; Setacci, Carlo; Palasciano, Giancarlo
ABSTRACT: Introduction: Optical Coherence Tomography (OCT) is an intravascular imaging providing high-resolution images of morphological features of arterial wall. Nowadays, OCT is an accepted intravascular modality to study coronary arteries, stent implantation, and vessel injury. In the last decade, an increasing interest have been focused on the application of OCT in carotid arteries. Areas covered: Literature evidence in the application of OCT in carotid arteries still remains debated. So far, OCT has been used as a research tool, aiming to evaluate atherosclerotic plaques' features and stents' behavior after implantation. This paper is intended to summarize clinical evidences and practices in the use of OCT in carotid arteries district and during CAS procedures. Literature review was completed via Pubmed search using Keywords. Expert opinion: CAS is a safe and effective procedure when performed by trained physicians with a tailored approach. In this scenario, ambiguous pictures at ultrasound, angiography, and IVUS might be clarified using OCT. By providing unprecedented microstructural information on atherosclerotic plaques, OCT may identify the features of vulnerable carotid plaque and, by identifying possible defects after stent implantation as malapposition and plaque prolapse, it may help the tailoring approach to CAS.